Bahasa Inggris - Alfiani, Sulis; Priantina, Anita (Airlangga Journal of Innovation Management, 2024)
This research aims to explore the factors influencing consumers' purchasing intentions at halal-labeled restaurants, especially among Millennials in Bogor. By adopting the Theory of Planned Behavior (TPB) as a conceptual framework, this study is limited to a sample scope involving 222 respondents aged 20-39 who practice Islam, including both students and private sector individuals residing in Bogor City. This study used the SEM-PLS method in analyzing the data. It is conducted in two stages, the evaluation of the measurement model (outer model) and the evaluation of the structural model (inner model). The Path Coefficients method has been employed to assess the direct effects of an exogenous latent construct or variable on an endogenous latent variable. The research results show that attitude variables and halal labels have a significant influence on consumer buying interest in halal restaurants, while knowledge and price variables do not have a significant influence on buying interest. The implications of this research are highly relevant for halal restaurant industry owners and practitioners. Strategic recommendations include enhancing information about the halalness of products and services and strengthening halal certification and labels. Restaurant owners are encouraged to seek a balance between competitive pricing and high-quality service. Focus on improving consumer knowledge about the halal status of products, enhancing brand image, and emphasizing the halal label as a positive differentiator.